2015
DOI: 10.15666/aeer/1301_181192
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee (Apis Mellifera) Mediated Increased Reproductive Success of a Rare Deceptive Orchid

Abstract: Georgikon Faculty, Festetics u. 7., Hungary,Abstract. Honeybees are the most numerous and significant among insect pollinators, but despite their significance their potential role in increasing the reproductive success of threatened European orchids remains largely unexplored. In this study we aim to evaluate the effect of apiary proximity on the fructification rate of the rare and endangered Adriatic Lizard Orchid (Himantoglossum adriaticum H. Baumann). To do so, first we quantified the reproductive success (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…The fruit trees of the Csatár Hill were not blossoming at the time of early P. grandis flowering, so the studied flowers were the only pollen sources for Apis mellifera. The significant role of honey bees in successful fructification was observed in the case of later flowering orchid species as well (Biró et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…The fruit trees of the Csatár Hill were not blossoming at the time of early P. grandis flowering, so the studied flowers were the only pollen sources for Apis mellifera. The significant role of honey bees in successful fructification was observed in the case of later flowering orchid species as well (Biró et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…m e l l i f e r a p o l l i n a t o r s i n t h e Kapitańszczyzna and Skupowo areas might be a consequence of the many apiaries in close proximity to D. majalis populations. Biró et al (2015) showed that A. mellifera is a significant pollinator promoting higher reproductive success in the deceptive Himantoglossum adriaticum (Orchidaceae) population near the honey bee apiary. We did not consider A. mellifera as a Bnative^pollinator in an evolutionary sense, but rather a widely introduced, super-generalist species that occupies a central role in many pollination networks (Medan et al 2006;Russo 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Eight species of the solitary bee Andrena have been reported as visiting H. hircinum , together with representatives of five further bee genera plus the beetle genus Oedermera (e.g., Teschner, 1980; Vöth, 1990; Kropf & Renner, 2008). A similar but slightly narrower range of bees are known to visit H. adriaticum (Claessens & Kleynen, 2011; Biró et al, 2015), including the social honey bee Apis mellifera —a species that has also been witnessed visiting H. caprinum and H. jankae . Unsurprisingly, compared with visitors to subgenus Himantoglossum , bees observed visiting subgenus Barlia flowers are on average larger bodied; they encompass at least six species of four genera, most commonly Bombus (Teschner, 1977; Claessens & Kleynen, 2011).…”
Section: Discussionmentioning
confidence: 99%